Supporter influence on club governance in a sports league: A utility maximization model - Paul Madden; Terry Robinson (The University of Manchester, Manchester Business School, 2010)
Motivated by increasing supporter involvement in club governance in English football, the paper presents a simple model of a sports league in which club objectives are utility functions defined over profits, win percentages and fan (=supporter) welfare, formalising a seminal suggestion of Sloane (1971). Consequences of increased utility weight on fan welfare (capturing increased supporter involvement in governance) are unambiguously higher attendances, with more nuanced affects on ticket prices and player expenditure. The attendance affect is consistent with some limited, anecdotal data currently available from clubs with existing supporter boardroom representation. Normatively, positive profits for club owners indicate social sub-optimality.
Keywords: L10; L83; 330